The importance of knowledge management in supporting research and development in an academic library - Samsuddin, Samsul Farid (Persatuan Pustakawan Malaysia, 2012)
Research and development (R&D) is very common nowadays in which an organization can experience future growth by developing new products or processes to improve and expand their operations. Knowledge management environment, can either lead to the development of new products or procedures, or to the improvement of existing products or procedures. The aim of this paper is to describe the importance of knowledge management in an academic library in supporting the library’s mission which is to provide excellent resources, services and facilities to support the customer’s requirement in enhancing learning, teaching, research and consultancy activities. Academic libraries especially those belonging to research universities should implement knowledge management in enhancing and expanding research based services to the university’s community.